Short‐term trained lexical categories affect preattentive shape perception: Evidence from vMMN. (3rd December 2016) - Yu, Mengxia; Mo, Ce; Zeng, Tianyu; Zhao, Sasa; Mo, Lei
Abstract: Perceptual processing of colors and shapes in the right visual field is modulated by the lexical category information of the stimuli, a phenomenon known as the lateralized Whorfian effect. For color stimuli, lateralized Whorfian effect is characterized by preattentive occurrence and dependency on acquired lexical information, but it remains unknown whether these key features are generalizable to other domains of perceptual processing. Here, we investigated whether lateralized Whorfian effect in the shape perception domain also depends on acquired lexical category and occurs preattentively using ERPs. Participants were trained to associate novel, irregular polygons with lexical category labels via short‐term intensive training. Using the visual oddball paradigm, we found stronger visual mismatch negativity (vMMN) component elicited by the deviant stimuli whose lexical category differed from the standard stimuli when the deviant was presented in the right visual field, indicating higher perceptual conspicuity for between‐category stimuli. These findings provide direct evidence of similar preattentive lexical category‐contingent modulation on shape perception akin to color perception, suggesting that the lateralized Whorfian effect is not epiphenomenal but rather might reflect the interaction between higher‐level lexical processing and the lower‐level perceptual processing more broadly.